MyEvent4U platform: A conceptual digital solution - Azahari, Nur Faizah; Khamis, Shaidatul Addilla; Daud, Nursheera Lissa; Ahmad Dahlan, Abdul Rahman (Research Publish Journal, 2018)
The purpose of this paper is to help people by providing them with an event planner that will plan everything that they needed on behalf of them. MyEvent4U is a business model platform which provides an event planning. Event planning is the process of planning a ceremony, festival, party or just about any events. It includes budgeting, selecting the dates and venue. With the help of social media tools, it enables us to plan an event even better. MyEvent4U is a Consumer-to-Customer (C2C) business model which aims to provide a conceptual solution of events planning and management. The methodologies that we are using for this paper are nine blocks of Business Model Canvas (BMC) framework, Value Proposition Canvas (VPC) [1], interview and survey.